THE EFFECT OF MIND MAPPING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT - Fauziah Muhlisa and Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study deals with The Effect of Mind Mapping Technique on Students’ Achievement in Writing Narrative Text at SMAN 4 Medan. The objective of this study was to find out if there was a significant effect of mind mapping technique on students’ achievement in writing narrative text. It was conducted by using experimental research. The population of this study was the eleventh grade students of SMAN 4 Medan which consists of six parallel classes. Two classes were taken as the sample of the research, XI-1 IPA and XI-5 IPA. The class XI-1 IPA was an experimental group and class XI-5 IPA was a control group. The experimental group was taught by Mind Mapping Technique, otherwise the control group was taught by using lecturing technique or without used Mind Mapping Technique. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. It was found that t-observed (5.63) higher than t-table (2.00). It means that there was a significant effect on students’ achievement in writing narrative text at SMAN 4 Medan by using mind mapping technique.